EFEKTIVITAS STRATEGI PROMOSI BPJS KETENAGAKERJAAN KANTOR CABANG BANDAR LAMPUNG DALAM MENINGKATKAN KEPESERTAAN PADA PEKERJA SEKTOR INFORMAL - Pusvitha, Ida Vivi; Ali, Suprihatin (Jurnal Kompetitif Bisnis, 2023)
The purpose of this study was to determine the effectiveness of promotional strategies in increasing the participation of informal sector workers at the Bandar Lampung branch of Employment BPJS. Regarding the method, this type of research uses a survey method with a quantitative approach. Judging from the research objectives, this research is descriptive using purposive techniques. The population of this research is informal workers who are registered with BPJS Ketenagakerjaan Bandar Lampung Branch. The number of samples in this study were 100 respondents and the data were obtained using a questionnaire. Descriptive statistical analysis was used as an analytical tool in this study. The results showed that the promotion strategy used by the BPJS Ketenagakerjaan Bandar Lampung Branch Office consisting of advertising had an average value of 3.044 which was in the scale range of the moderately effective category, personal selling with an average value of 4.052 was in the effective category, direct marketing had an average value of 4.003 with an effective category, PR entered the effective category with an average of 3.58 and word of mouth entered the effective category with an average of 4.06. In this case, BP Jamsostek Bandar Lampung needs to increase its advertising efforts through social media and reach out to non-wage earners.